Effective Recreational Activities in Urban Green Spaces for Mental Health of Scientific Researchers - Jinshan Yan; Yashi Wu; Guofan Shao; Quanyi Qiu; Lina Tang (Ecosystem Health and Sustainability, 2024)
Scientific researchers are known for their demanding intellectual efforts and are particularly susceptible to mental health disorders. Urban green spaces (UGSs) are beneficial for people’s mental health, yet there is limited research on what types of UGSs and activities are effective for improving researchers’ mental health. Here, we investigate if researchers’ mental health can be enhanced by visiting affiliated green spaces, pocket parks, comprehensive parks, and coastal beaches. The research hypothesis was that the natural and social pathways of recreational ecosystem services jointly reduce researchers’ mental stress and attentional fatigue. The results suggest that nature contact, nature connectedness, and social interaction directly or indirectly have positive impacts on scientific researchers’ mental health. Both nature connectedness and social interaction serve as crucial mediating variables between nature contact and mental health. In terms of direct impact, high-frequency recreational activities in small UGSs with high accessibility, markedly  relieve stress, whereas visit frequency in large UGSs with low accessibility has a limited effect on long-term mental stress relief. In terms of indirect impact, small UGSs alleviate attentional fatigue through the mediation of nature connectedness, while large UGSs mainly mitigate mental stress and attentional fatigue through the mediation of social interaction. This study provides a natural-social integrated perspective on recreational ecosystem services to enhance the well-being of scientific researchers. We provide recommendations for researchers to mitigate work-related stress and fatigue and to offer information useful for decision-making support to create a healthy environment for scientific researchers.